A questão do negro no curso de graduação em serviço social da Universidade Federal Fluminense - Silva Filho, José Barbosa da (2004)
The research "The Question of the Black Man in the Course of Graduation in Social Service of Fluminense Federal University" intends to collaborate with the debate around the questions that respect says the situation of the black population in the Brazilian society, victim for the violence of the description-cultural preconception, the partner-racial discrimination and the economic exclusion in its interaction with the other segments of the Brazilian population. Our work if bases on the hypothesis of that still existing the racist and racialistas positions in our society are strengthened by the unfamiliarity of the historicalculture- social and religious origins of the African black of the diáspora and of the Brazilian black on the part of the professionals whom they daily deal with this segment of the population. In the specific case of our reflection, we will study the professionals in Social Service formed by Fluminense Federal University - UFF. The question that in interested them to clarify age: being professional that most invariable percentage of black color and mediums brown interact with parcels of the population where are great, the knowledge that the Socia l Assistants graduated by the UFF receive in its process of formation, contemplate and problemate subjects related with the questions that say respect to the black in the Brazilian society? In negative case, why this occurs? To materialize this intention analyses had been carried through: a) in the Works of Conclusion of Courses (TCCs) of graduated Social Service for the UFF of 1948 at 2002; b) in publications directed for the Social Assistants; c) in the curricular gratings of the Courses of Formation in Social Service of the UFF, the UERJ, the UFRJ and the PUC -RJ. Also interviews with Professors of the ESS-UFF had been analyzed and in the questionnaires distributed between students. These metodology procedures had answered our question and the negative premise became true. The reasons and the reasons meet explain in this final report.